Catalytic oxidation of organic sulfides by new iron-chloro Schiff base complexes: The effect of methoxy substitution and ligand isomerism on the electronic, electrochemical and catalytic performance of the complexes. (15th May 2021) - Aghvami, Fatemeh; Ghaffari, Abolfazl; Kucerakova, Monika; Dusek, Michal; Karimi-Nami, Rahman; Amini, Mojtaba; Behzad, Mahdi
Graphical abstract: Four new iron-chloro Schiff base complexes were used as catalyst for selective oxidation of sulfides and the results are discussed based on the presence of OMe substitution and ligand isomerism. Abstract: Four new Fe(III)-Chloro Schiff base complexes were synthesized and characterized. The N2 O2 type tetradentate Schiff base ligands were synthesized from the condensation of meso -1, 2-diphenyl-1, 2-ethylenediamine with salicylaldehyde (H2 L 1 ), 3-methoxysalicylaldehyde (H2 L 2 ), 4-methoxysalicylaldehyde (H2 L 3 ) and 5-methoxysalicylaldehyde (H2 L 4 ) . The corresponding iron-chloro complexes with the general formula [Fe(L n )Cl] (n = 1–4 for complexes (1 –4) ) were characterized by FTIR and UV–Vis spectroscopy and elemental analysis. Crystal structure of (1) was obtained by single-crystal X-ray crystallography. Cyclic voltammetry was used to study the electrochemistry of the complexes. The complexes were used as catalysts for the selective oxidation of organic sulfide compounds to sulfoxides. High catalytic performance and selectivity were obtained. The spectroscopic, electrochemical and catalytic data are discussed based on the electronic, steric and electrochemical properties of the complexes.